Theranostic applications of organic nanoparticles for cancer treatment - Yhee, Ji Young; Son, Sohee; Kim, Namho; Choi, Kuiwon; Kwon, Ick Chan (CAMBRIDGE UNIV PRESS, 2014)
Research in nanotechnology-based molecular imaging and targeted drug delivery has resulted in a noticeable progress in cancer theranosis, the simultaneous application of cancer therapy and diagnosis. Theranostic nanoparticles (NPs) have been developed using diverse base materials, and organic materials are of major interest in the synthesis and preparation of these NPs. A variety of organic NPs have their own advantages, depending on the physiochemical and biological properties of the base materials. This article reviews recent developments in organic NPs, which are grouped into four major kinds of base materials: lipids, polysaccharides, peptides/proteins, and synthetic polymers. The advantageous properties of frequently used base materials and practical performance of the various organic NPs in vivo are discussed. These theranostic NPs offer new opportunities for effective cancer treatment.
Keywords: GLYCOL CHITOSAN NANOPARTICLES; SOLID LIPID NANOPARTICLES; DRUG-DELIVERY SYSTEMS; TUMOR-BEARING MICE; HYALURONIC-ACID NANOPARTICLES; ENHANCED GENE DELIVERY; HUMAN SERUM-ALBUMIN; IN-VIVO NIRF; POLYMERIC NANOPARTICLES; POLY(ETHYLENE GLYCOL)